Proceedings of the 12th Workshop on Computational Approaches to Subjectivity, Sentiment &Amp; Social Media Analysis 2022
DOI: 10.18653/v1/2022.wassa-1.20
|View full text |Cite
|
Sign up to set email alerts
|

WASSA 2022 Shared Task: Predicting Empathy, Emotion and Personality in Reaction to News Stories

Abstract: This paper presents the results that were obtained from WASSA 2022 shared task on predicting empathy, emotion, and personality in reaction to news stories. Participants were given access to a dataset comprising empathic reactions to news stories where harm is done to a person, group, or other. These reactions consist of essays and Batson's empathic concern and personal distress scores. The dataset was further extended in WASSA 2021 shared task to include news articles, person-level demographic information (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…The Pearson correlation between the human evaluations and our predicted score is 0.72. We have seen that the Pearson correlation scores produced (Barriere et al, 2022). by our approach are comparatively higher as compared to the previous studies done on humanannotated scores for learning.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…The Pearson correlation between the human evaluations and our predicted score is 0.72. We have seen that the Pearson correlation scores produced (Barriere et al, 2022). by our approach are comparatively higher as compared to the previous studies done on humanannotated scores for learning.…”
Section: Resultscontrasting
confidence: 56%
“…by our approach are comparatively higher as compared to the previous studies done on humanannotated scores for learning. SINAI, CAISA, and LingJing are teams belonging to WASSA 2022 shared task (Barriere et al, 2022) (Table 4). We tested six models during inference time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common approach is to predict the emotion or persona from a pre-defined set and generate the response in a multi-task manner (Ma et al, 2021;Sabour et al, 2022;. Besides that, lots of work notices these linguistic cues underneath text by directly predicting them independently as a classification task Barriere et al, 2022;Ghosh et al, 2022). Distinguishing from these previous works, we regard different aspects of cues as part of user status and prompt the LLMs to reason user status exhibited in the dialogue context, aiming to generate more helpful and acceptable responses for users.…”
Section: Related Workmentioning
confidence: 99%
“…Personality. Previous works found that the content and style of a user's inquiry can provide indirect insights into their personality traits (Mairesse et al, 2007;Barriere et al, 2022). For instance, an individual with a tendency towards anxiety may ask for advice on how to alleviate nervousness before an upcoming job interview, phrasing the question as follows: "What strategies can I employ to reduce my anxiety and perform well in tomorrow's interview?".…”
Section: Datasets Collectionmentioning
confidence: 99%